Reperfusión Temprana en el infarto agudo de miocardio. Hospital de Especialidades Carlos Andrade Marín. Quito, 2018-2019 - Luna Salazar, Joselyn Fernanda (2019)
In Ecuador, cardiovascular diseases, including acute myocardial infarction, are among the leading causes of general mortality, and their incidence is increasing due to accelerated changes in the population's life profiles. People suffering from acute myocardial infarction have a high probability of dying in the first hours after the event. However, upon receiving reperfusion treatment at an early stage, the probability of normalizing cardiac function and decreasing the mortality rate is similarly high. Therefore, spreading the need for recognition of symptoms by patients, early access to specialized services and timely treatment, reaches a public health importance in our country. Objectives: To analyze the number of patients with acute myocardial infarction with ST segment elevation who received early reperfusion treatment in the HECAM emergency area in the period between October 2018 - April 2019 Material and Methods: This is a cross-sectional, periodical study with prospective collection of information, carried out between October 2018 and April 2019. The electronic medical records consigned in the AS400 system were studied of all patients admitted to the Hospital. Carlos Andrade Marín from Quito with a diagnosis of Acute Myocardial Infarction. Results: The results show that only 29% of the patients admitted received attention within the first six hours from the onset of symptoms. 81% of patients undergoing myocardial reperfusion procedure did not suffer complications; 9% of patients undergoing reperfusion procedure, died, these numbers suggest a relative safety of the procedure. Conclusions: The importance of early myocardial reperfusion in patients who have suffered an acute myocardial infarction has been widely documented worldwide and timely access to emergency services is needed where more knowledge and action must be implemented in a timely manner. in acute myocardial infarction paying more attention to patients suffering from ST segment elevation especially in male patients of the third. In the same way, there is a need for coverage and resolution capacity of the services of the National public health network.